RI 7021 Process Development In Removing Sulfur Dioxide From Hot Flue Gases (In Four Parts) 3. Pilot Plant Study of the Alkalized Alumina System for SO2 Removal - D. Bienstock (The National Institute for Occupational Safety and Health (NIOSH), 1967)
The use of alkalized alumina in removing sulfur dioxide from a coal-combustion flue gas at 625° F was investigated on a pilot plant scale. The absorber was 26 feet long and 1.6 inches ED. Counter-current gas-solids flow at gas velocities of 8 to 15 ft/sec in the presence and absence of baffles, as well as solids entrainment at gas velocities of 20 to 23 ft/sec with solids recycle, were employed. The spent absorbent as regenerated as fixed bed with the reducing gases--reformed natural .7.7d hydrogen. Of absorption-regeneration were successful completed using the alkalized alumina rolled into spherical granules 10 to 16 mesh. There was no loss in activity of absorbent toward SO2 with a modest attrition equivalent to 0.l percent of the solids feed. Supporting studies were conducted on the effect of the sodium content in the absorbent, the composition of the reducing gas, thermal treatment to increase absorbent hardness, and removal of absorbed chlorine from the absorbent. A mathematical model was formulated to describe the removal of SO2 by alkalized aluminum from fixed and falling beds.